Inside Cover: Ammonothermal Synthesis of Novel Nitrides: Case Study on CaGaSiN3 (Chem. Eur. J. 11/2017). Issue 11 (27th December 2016) - Häusler, Jonas; Neudert, Lukas; Mallmann, Mathias; Niklaus, Robin; Kimmel, Anna‐Carina L.; Alt, Nicolas S. A.; Schlücker, Eberhard; Oeckler, Oliver; Schnick, Wolfgang
Abstract : New high‐temperature autoclaves were developed for the ammonothermal synthesis of innovative multinary nitrides. The cover picture shows various in‐house manufactured autoclave components made of a nickel‐based superalloy. Using this equipment the first nitridogallosilicate CaGaSiN3 was synthesized. Eu 2+ ‐doped samples show red luminescence with an emission maximum of 620 nm when irradiated with UV light. Selected area electron diffraction (SAED) patterns on single crystals were recorded, which are represented in the background. More information can be found in the Full Paper by W. Schnick et al. onpage 2583 ff.